Long Time Error Analysis of Finite Difference Time Domain Methods for the Nonlinear Klein-Gordon Equation with Weak Nonlinearity (Communications in Computational Physics, 2019)
We establish error bounds of the finite difference time domain (FDTD) methods for the long time dynamics of the nonlinear Klein-Gordon equation (NKGE) witha cubic nonlinearity, while the nonlinearity strength is characterized by ε2 with 0
Keywords: Nonlinear Klein-Gordon equation; finite difference time domain methods; long time error analysis; weak nonlinearity; oscillatory nonlinear Klein-Gordon equation.